Entrance, Swastik Court - Ghosh, Ayan (Jio Institute, 2023)
Swastik Court, 132 Maharshi Karve Road, Churchgate. Designed by the architectural firm Sykes, Patkar & Divecha. Varjiwandas Motilal Saraiya, the original owner, named the building ‘Swastika’, an auspicious symbol widely revered in several South Asian cultures.